2021
DOI: 10.1186/s12885-021-08643-5
|View full text |Cite
|
Sign up to set email alerts
|

The association of minerals intake in three meals with cancer and all-cause mortality: the U.S. National Health and Nutrition Examination Survey, 2003–2014

Abstract: Background Intake time of diet has recently been demonstrated to be associated with the internal clock and circadian pattern. However, whether and how the intake time of minerals would influence the natural course of cancer was largely unknown. Methods This study aimed to assess the association of mineral intake at different periods with cancer and all-cause mortality. A total of 27,455 participants aged 18–85 years old in the National Health and N… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 66 publications
0
7
0
Order By: Relevance
“…In the case of minerals and their optimal intake timing, a cohort study has found that evening intake of potassium, calcium, and magnesium reduced the risk of cancer and all-cause mortality, which aligns with each mineral's corresponding metabolic rhythms. [91] This was in contrast to morning and afternoon intake, in which no significant associations were observed. With regards to cardiometabolic health, balancing potassium intake with circadian rhythms of potassium homeostasis, particularly its absorptivity and excretion rhythms-may improve potassium retention and the regulation of membrane polarization, which potentially extends to glucose and lipid intestinal absorption, metabolism, as well as blood pressure regulation, [91] although the exact mechanisms is yet to be established.…”
Section: Micronutrientsmentioning
confidence: 80%
See 1 more Smart Citation
“…In the case of minerals and their optimal intake timing, a cohort study has found that evening intake of potassium, calcium, and magnesium reduced the risk of cancer and all-cause mortality, which aligns with each mineral's corresponding metabolic rhythms. [91] This was in contrast to morning and afternoon intake, in which no significant associations were observed. With regards to cardiometabolic health, balancing potassium intake with circadian rhythms of potassium homeostasis, particularly its absorptivity and excretion rhythms-may improve potassium retention and the regulation of membrane polarization, which potentially extends to glucose and lipid intestinal absorption, metabolism, as well as blood pressure regulation, [91] although the exact mechanisms is yet to be established.…”
Section: Micronutrientsmentioning
confidence: 80%
“…[ 91 ] This was in contrast to morning and afternoon intake, in which no significant associations were observed. With regards to cardiometabolic health, balancing potassium intake with circadian rhythms of potassium homeostasis, particularly its absorptivity and excretion rhythms—may improve potassium retention and the regulation of membrane polarization, which potentially extends to glucose and lipid intestinal absorption, metabolism, as well as blood pressure regulation, [ 91 ] —although the exact mechanisms is yet to be established.…”
Section: Dietary Components Intake Timing and Their Interaction With ...mentioning
confidence: 92%
“…In nutritional epidemiology, food substitution models have been used to study the relationship between nutrient or food substitution and related health or disease outcomes and offer dietary advice for the prevention and treatment of diseases [30]. Today, many studies have recognized and used the method of substitution analysis to study the substitution of one food or nutrient with another under the premise of equal energy or equal intake, and then observed changes in epidemiological indicators [5,31,32]. Based on the CPH model mentioned above, we established an equivalent dietary fiber substitution model to evaluate the changes in all-cause and cancer mortality risks caused by switching dietary fiber intake from a single time period to another single time period.…”
Section: Discussionmentioning
confidence: 99%
“…As a result, research in the field of nutrition has created the concept of chrono-nutrition, which posits that when you eat is as important as what you eat [2]. A growing body of animal and human studies have shown that the timing of energy, macronutrient, and micronutrient intake had an influence on biological clocks and circadian rhythms, which are associated with the development of cancer and CVD [3][4][5][6][7]. However, to date, whether and how the intake time of dietary fiber could impact the health of humans remains largely unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Some minerals, such as zinc, selenium, magnesium, vanadium, and germanium, are connected to human health and cancer prevention among the multitude of essential and non-essential minerals (Singh et al 2012). The immune system is the natural mechanism that defends against cancer (Xu et al 2021), and minerals supplement it. Numerous population studies have discovered that dietary mineral intake may in uence the development of some cancers.…”
Section: Role Of Minerals In Chemopreventionmentioning
confidence: 99%